عزل وتحديد كثافة بعض أنواع الجراثيم المحمّلة في هواء ومحيط حظائر الدواجن - العيسى بشرى (Latakia University Journal -Biological Sciences Series, 2014)
- تم تطبيق طريقة الترسب الجرثومي فوق الأوساط الجرثومية الصلبة لكشف انتقال الجراثيم مع الهواء بواسطة القطيرات والغبار العضوي بين حظائر الدواجن في بعض مزارع دجاج اللحم والبيض بعد تحديد مستوى الحمولة الجرثومية ضمن الحظائر. - لوحظ في هذه الدراسة أن أغلب المزارع المدروسة لم تطبق شروط الرعاية والتربية الصحيحة من ناحية التهوية والخدمة مما أثر ايجاباً على نمو وتكاثر الجراثيم وازدياد الحمولة الجرثومية وتناسب مستوى التلوث طرداً مع ارتفاع درجات الحرارة والرطوبة بالنسبة لبعض الجراثيم ومنها الجراثيم العنقودية والعقدية. - كما بينَّت النتائج في تصنيف العزلات تبعاً لاختبارات الـ API انتماء الجراثيم للمكورات العنقودية ((Staphylococcus xylosus, Staphylococcus aureusوالعصيات القولونية Escherichia coli والهيموفيلس (Homophilesparagallinarum). كما سُجّل انتقال للعدوى وتشخيص إصابات مرضية متوافقة مع العزلات الجرثومية من هواء البيئة المحيطة بقطعان الدواجن في الحظائر المتجاورة ضمن المزارع المدروسة. - Bacterial deposition method was applied over hard to detect microbial community transmission of the germs with air by droplets and dust combine in some poultry farms chicken broiler and hen layer after determining the level of the microbial load in the barns. - Observed in this study that most of the farms studied the conditions did not apply the proper care and education in terms of ventilation and servicewhich impact positively on the growth and reproduction of bacteria and increased bacterial load and fit the level of contamination parcels with high temperatures and humidity for some bacteria, including Staphylococcus and Streptococcus. - As results showed in the classification of isolates according to the api that tests for Staphylococcus aureus bacteria (Staphylococcus xylosus Staphylococcus aureus), Escherichiacoli and (Homophilesparagallinarum) Also transmission of infection and diagnosis of injury satisfactory bacterial isolates from compatible ambient air in poultry flocks in adjacent pens in farms.